Option Value: Empirical Evidence From a Case Study of Recreation and Water Quality: Comment - Mitchell, Robert Cameron; Carson, Richard T. (Quarterly Journal of Economics, 1985)
Robert Cameron Mitchell, Richard T. Carson; Option Value: Empirical Evidence from a Case Study of Recreation and Water Quality: Comment*, The Quarterly Jou